The city of Ugarit at Tell Ras Shamra - Yon, Marguerite (Eisenbrauns, 2006)
"In 1929, a farmer accidentally discovered a tomb near the Mediterranean coast of Syria, about 12 km north of the modern seaport of Latakia. Initial excavations at the tell of Ras Shamra by Rene Dussaud and Claude Schaeffer brought to light impressive architectural remains, numerous artifacts, and tablets written in cuneiform (both alphabetic and syllabic), and the excavators soon were able to identify the site as the ancient city of Ugarit. Much of the material remains came to be dated to the end of the Late Bronze Age, from the 14th century through the 12th century b.c.e., and the religious, economic, and mythological texts from that era have had a major effect on our understanding of the history of the late 2nd millennium. However, by that time the site had already seen more than 6,000 years of occupation, and the data from Ras Shamra - Ugarit thus have become important as a reference point for the early history of the Near East along the Levantine coast and the eastern Mediterranean." "In this volume, Marguerite Yon, the principal investigator since the early 1970s on behalf of the French archaeological team, brings us up to date on the 70-year-long excavation of the site. During the past 25 years, much of our understanding of the site itself has changed, due to new excavations, reexcavation, and reinterpretation of prior excavations. This volume is the authoritative latest word on the data from the site and their meaning for our understanding of the importance of ancient Ugarit."--Jacket.